2021
DOI: 10.1111/cars.12326
|View full text |Cite
|
Sign up to set email alerts
|

BB see: Transparency legislation and public discussions of wage inequality

Abstract: Disparities in compensation persist between men and women. Wage transparency, which enables workers to compare their compensation to what others receive in their organization, can be an important tool for redressing specific intra‐firm disparities tied to discriminatory processes. Drawing on newspaper reports about gender pay differentials, we provide the first analysis of whether a public disclosure of pay transparency corresponds to a shift in broader public discourse, as represented by news coverage. Themat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Unfair pay discrimination continues to be a persistent issue globally (Treleaven & Fuller, 2021), and one of the key measures worldwide to address pay discrimination is legislation (Heymann et al, 2020). Heymann et al (2020) note that the impact of anti-discrimination laws has not been widely researched and recommend that future studies include less industrialised countries, such as those in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Unfair pay discrimination continues to be a persistent issue globally (Treleaven & Fuller, 2021), and one of the key measures worldwide to address pay discrimination is legislation (Heymann et al, 2020). Heymann et al (2020) note that the impact of anti-discrimination laws has not been widely researched and recommend that future studies include less industrialised countries, such as those in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Using transparency as a tool to drive positive social change can be highly effective. In recent years, for example, a focus on pay transparency-whereby an openness about remuneration empowers workers to benchmark their compensation against others at a similar level within their organisation-has enabled the successful detection of systemic pay inequalities (Heisler 2021;Treleaven and Fuller 2021). Research has shown that wage transparency can have the twofold impact of reducing gender pay gaps, while also 1 See e.g.…”
Section: Introductionmentioning
confidence: 99%
“…sparking productive public conversations about inequality (Treleaven and Fuller 2021). 1 Yet alongside the advantages to integrating a transparent approach within equality initiatives, transparency also has its limitations and challenges.…”
Section: Introductionmentioning
confidence: 99%